The Law as Regulator of the Ideological Discourse of Fraternity in a Post-Liberal Society - Silva Ferraz, Adilson (DIXI, 2015)
Ths text aims to show that there is a gap between fraternity in its utopian (ideal) sense and its practical (real) sense. Th utopian sense is customarily used as the basis for the practical sense and can discursively be manipulated for any practical purpose, even against human rights. We call this the “ideological discourse of fraternity”. We explain that fraternity exists dialectically and is defied rhetorically like other phenomena. Th dialectic explains fraternity based on the idea of “fraternal openness”, and a special phenomenon that acts in the mutual recognition between individuals and in the resignifiation of otherness. We then present themain thesis: the inclusion of fraternity as a legal element that can help to prevent the ideological discourse of law itself (when this is turned against fundamental rights) and serve as a barrier of containment for the ideological discourse of moral fraternity, even though there is always the risk that this may be used to deepen the gap between utopia and practice, by becoming a legal mechanism for social oppression
Keywords: law; fraternity; ideology; moral; utopia